Eksplorasi Etnomatematika pada Arsitektur Melayu : Studi Geometri di Istana Maimun - Nazwa Dewi Tianda; Delfi Wulandari; Lidwina Roulina Turnip; Safana Nur Rizky; Mardiyah Kharismayanda; Elvi Mailani (Universitas Maritim AMNI Semarang, 2024)
Ethnomathematics as a study bridges mathematics with local cultural contexts, including traditional architecture. Istana Maimun, a cultural heritage of the Malay people, holds a wealth of geometric elements that reflect local wisdom and cultural values. This research aims to explore the geometric aspects of Istana Maimun's architectural design through an ethnomathematical approach. The study identifies patterns of symmetry, proportions, and geometric functions applied in architectural elements such as ornaments, spatial layouts, and building structures. The analysis reveals that the geometry in Istana Maimun's architecture not only serves an aesthetic purpose but also carries philosophical meanings closely tied to Malay cultural identity. This research is expected to contribute to the development of ethnomathematics studies and the preservation of local wisdom.